The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1365-2745.12206
|View full text |Cite
|
Sign up to set email alerts
|

Functional attributes change but functional richness is unchanged after fragmentation of Brazilian Atlantic forests

Abstract: Federal de Vic ßosa, Vic ßosa, Minas Gerais, Brasil Summary 1. Fragmentation of tropical forests is one of the greatest threats to global biodiversity. Understanding how biological and functional attributes of communities respond to fragmentation and, in turn, whether ecosystem functioning is impacted upon are critical steps for assessing the long-term effects and conservation values of forest fragments. Ecosystem functioning can be inferred through functional diversity metrics, including functional richness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
201
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(241 citation statements)
references
References 78 publications
19
201
1
12
Order By: Relevance
“…We used the metrics proposed by Villéger et al [27], because they are independent from each other (Pearson r ¼ 20.02, p ¼ 0.89), are easy to calculate [42] and are often used in the literature (e.g. [7,8,11]), which makes our results more comparable to other studies. Higher values for these metrics correspond to higher functional trait diversity.…”
Section: (E) Functional Trait Diversitymentioning
confidence: 89%
See 1 more Smart Citation
“…We used the metrics proposed by Villéger et al [27], because they are independent from each other (Pearson r ¼ 20.02, p ¼ 0.89), are easy to calculate [42] and are often used in the literature (e.g. [7,8,11]), which makes our results more comparable to other studies. Higher values for these metrics correspond to higher functional trait diversity.…”
Section: (E) Functional Trait Diversitymentioning
confidence: 89%
“…Current knowledge, however, does not point to a simple pattern, as some studies have found that functional diversity remained unchanged or was even positively affected (e.g. [5,[8][9][10][11]). Existing evidence thus suggests that the consequences of environmental changes for ecological functions are complex and far from being well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibited regeneration may have consequences for the future of altered riparian zones, but it remains to be seen if reductions in seedling and sapling abundance will propagate to larger size classes of trees. Because tree longevity in tropical forests is high, reduced seedling and sapling abundance suggests the possibility of an extinction debt, or inevitable future extinctions caused by past events (Magnago et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Devido à influência desses mapas sobre a organização de iniciativas oficiais de conservação e pesquisa da biodiversidade, desde então muitos estudos ecológicos têm optado por retratar a Floresta de Linhares como uma "floresta ombrófila densa" ou dense rain forest (por exemplo, Oliveira- Magnago et al 2014). Todavia, na contramão dessa tendência, alguns estudos têm considerado observações de campo ou análises do clima local para adotar o termo "floresta estacional semidecidual" (por exemplo, Rolim & Nascimento 1997;Rolim et al 1999;Kindel & Garay 2002;Saiter et al 2015), uma denominação disponível no sistema de Veloso et al (1991).…”
Section: A Semideciduidade Ou a Perenidade Da Floresta De Linharesunclassified